A study on auxiliary steam reducing device in marine nuclear power plants. Issue 1 (January 2020) - Zhao, Huijing; Zhao, Guanhui; Ma, Rui
Abstract: The pressure reducing device is one of the important parts of the auxiliary steam system in marine nuclear power plants. The pressure of auxiliary steam is reduced to meet the requirements of users with low pressure steam of second-loop system. This paper proposes a new auxiliary steam pressure reducing device, which can reduce the pressure of auxiliary steam in a concentrated region, and then provide low pressure steam to users. The new auxiliary steam pressure reducing device decreases the size, simplifies the adjusting mode, and improves the stability and reliability of auxiliary steam system. At last, the unsteady-state simulation based on Jtop is carried out on the auxiliary steam pressure reducing system. The results show that, when the pressure of high-pressure steam at upstream is changed, the steam pressure is stable, which is provided to users with low pressure steam.